2006
DOI: 10.2118/90096-pa
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Oil/Water-Flow Tests in Horizontal, Hilly Terrain, and Vertical Pipes

Abstract: Summary Flow pattern, pressure drop, and water holdup were measured for oil/water flow in horizontal, hilly terrain (±0.5 and ±3°), and vertical pipelines at a temperature of approximately 35 (± 5) °C and a pressure of approximately 245 kPa using the large-scale multiphase-flow test facility of Japan Oil, Gas and Metals Natl. Corp. (JOGMEC). Test lines of 4.19-in. (106.4-mm) inner diameter (ID) and 120-m total length were used, which included a 40-m horizontal or hilly terrain (near-horizonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
2

Year Published

2009
2009
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 4 publications
6
24
2
Order By: Relevance
“…Cox (1985) and Alkaya (2000) observed that the transition from separated to dispersed flow occurs at lower velocities in downwardly inclined flows than in horizontal flow. In contrast to the current work stratified wavy flow pattern has been observed in downwardly inclined flows by other investigators (Cox, 1985;Alkaya, 2000;Oddie et al, 2003;Abduvayt et al, 2004;Rodriguez et al, 2006). This could be due to the different ranges of velocities, fluid properties and pipe geometries used in their experiments.…”
Section: Flow Pattern Mapscontrasting
confidence: 95%
See 1 more Smart Citation
“…Cox (1985) and Alkaya (2000) observed that the transition from separated to dispersed flow occurs at lower velocities in downwardly inclined flows than in horizontal flow. In contrast to the current work stratified wavy flow pattern has been observed in downwardly inclined flows by other investigators (Cox, 1985;Alkaya, 2000;Oddie et al, 2003;Abduvayt et al, 2004;Rodriguez et al, 2006). This could be due to the different ranges of velocities, fluid properties and pipe geometries used in their experiments.…”
Section: Flow Pattern Mapscontrasting
confidence: 95%
“…Alkaya (2000) reported that downward inclination enhance the dispersed water-in-oil flow pattern slightly so that it appears at lower mixture velocities at -5º. Stratified wavy flow pattern has been observed by Abduvayt et al (2004) and Rodriguez et al (2006). For two-phase oil-water pipe flow the pressure drop behavior with respect to oil-water ratio has been presented in a number of publications starting with the work of Charles et al (1961).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that at low upward inclination generally results in higher water hold-up than in horizontal flow giving higher slip ratios [5][6][7]. The relevant systems are described by Scott [5] at +15º and +30º, Lum et al [6] at +5º and Abduvayt et al [7] at +0.5º and +3º. The reported S values are in general above one, for upwardly inclined oilwater flows and show a good agreement with present observations.…”
Section: Water Hold-up and Slip Ratio Measurementssupporting
confidence: 89%
“…At low inlet water fraction (λ w =0.25), the oil, as the less dense phase, travels at a considerably higher velocity than the water, so that S is always above one for upwardly inclined flows. Previous studies indicate that at low upward inclination generally results in higher water hold-up than in horizontal flow giving higher slip ratios [5][6][7]. The relevant systems are described by Scott [5] at +15º and +30º, Lum et al [6] at +5º and Abduvayt et al [7] at +0.5º and +3º.…”
Section: Water Hold-up and Slip Ratio Measurementsmentioning
confidence: 99%
“…Effects of the mixture flow velocity on the slip velocity ratio and water holdup at a constant input water fraction (b W ¼ 0.5) in the small inclined flows from À58 to 58 (data from Kumar et al [6] ). Abduvayt et al [4] 8.1 14.0 20.5 116 Atmaca et al [5] 3.8 11.6 15.8 83 Flores et al [1] À8.0 8.3 10.0 89 Kumara et al [6] 1.6 15.5 31.5 22 Lum et al [7,8] À0.3 10.3 22.0 121 Mukherjee et al [2] À2.6 8.0 15.1 228 Oddie et al [23] À1.6 6.3 7.1 8 Rodriguez and Oliemans [9] 14.1 19.6 24.1 19 Rodriguez and Baldani [24] 36.2 38.7 25.1 17 Vigneaux et al [3] À11.0 11.1 6. 5 25 can give a reasonable performance with 98 % of the data having an average absolute error less than 20 %.…”
Section: Inclined Flowmentioning
confidence: 99%